Computer Aided Teaching of Industrial Management Subject-A Case Study - Shahabadkar, Pramod K.; Nandurkar, Keshav N.; Shahabadkar, Prashant K. (Journal of Engineering Education Transformations, 2006)
Utilization of Computers and Overhead Projector (OHP) as a tool for teaching and learning experimentation has increased significantly ill recent years, as computers have become more powerful and less expensive. Teachers can experiment Oil using alternative models of Teaching-Learning methods easily and effectively. But can the computers and OHP replace the traditional method of teaching by chalk and duster and do these tools really improve the students learning.? Also does the application of computer as a teaching media makes the Teaching-Learning process more effective and does it reduces the learning losses? Here in we describe the results of the experiments conducted at K.K. Wagh Institute of Engineering Education & Research, Nashik (formerly known as K.K. Wagh College of Engineering) while teaching the Industrial Management subject for IIIrd semester Production Engineering students four years between 2001-2004. The experiments were designed to understand if learning of Industrial Management subject was significantly affected by three treatments of teaching medias namely 1. Chalk and duster 2. OHP 3. Computer aided teaching. This paper focuses on the development of Computer Aided Teaching Tool (CATT) and also conclusions of the experiments.